Microstrip Patch Antenna with C Slot for 5G Communication at 30 GHz - Siddharth Kishore; A. R. Abdul Rajak (Emerging Science Journal, 2022)
A novel design of a 30 GHz microstrip line-fed antenna for 5G communication has been presented in this paper. 5G is the latest industry standard in mobile communication, which is designed to deliver higher data speeds, lower latency, greater network capacity, and higher reliability. It uses major parts of the mmWave spectrum (28 GHz to 40 GHz), allowing for a wide range of applications like mobiles, vehicles, medical devices, and other IoT networks. This mmWave network requires efficient antennas for its effective communication. Patch antennas use the function of oscillating their physical structure to the wavelength of the transmitting wave. Thus, higher efficiency can be achieved in the mmWave spectrum due to its proximity to the actual dimensions of the patch antenna, which also allows us to design antennas at small sizes and high reliability. The design in this report has a patch antenna with a centre frequency of 30 GHz. The antenna was optimized for this frequency based on the best reflection coefficient and gain while keeping the restraints of staying within the FR-2 band of 28 GHz to 33 GHz. The proposed antenna has been implemented using Rogers RT5880 substrate for high gain and performance across a wide range of frequencies. The feed is also accompanied by a quarter-wave feed cut for performance increase and impedance matching. The design has a gain of 8.45, with a reflection coefficient of -8 dB at a resonant frequency of 30 GHz. It shows great directivity of 5o and VSWR of 2.3 over a bandwidth of 3.5 GHz. It also employs a 0.4 mm C slot, which induces a dipole effect, thereby increasing the directivity and gain of the antenna. Hence, it is recommended for use in applications related to 5G mobile communication. Doi: 10.28991/ESJ-2022-06-06-06 Full Text: PDF